Symmetry forbidden morphologies and domain boundaries in nanoscale graphene islands. (22nd May 2017) - Parreiras, S O; Gastaldo, M; Moreno, C; Martins, M D; Garcia-Lekue, A; Ceballos, G; Paniago, R; Mugarza, A
Abstract: The synthesis of graphene nanoislands with tailored quantum properties requires an atomic control of the morphology and crystal structure. As one reduces their size down to the nanometer scale, domain boundary and edge energetics, as well as nucleation and growth mechanisms impose different stability and kinetic landscape from that at the microscale. This offers the possibility to synthesize structures that are exclusive to the nanoscale, but also calls for fundamental growth studies in order to control them. By employing high-resolution scanning tunneling microscopy we elucidate the atomic stacking configurations, domain boundaries, and edge structure of graphene nanoislands grown on Ni(1 1 1) by CVD and post-annealed at different temperatures. We find a non-conventional multistep mechanism that separates the thermal regimes for growth, edge reconstruction, and final stacking configuration, leading to nanoisland morphologies that are incompatible with their stacking symmetry. Whole islands shift their stacking configuration during cooling down, and others present continuous transitions at the edges. A statistical analysis of the domain structures obtained at different annealing temperatures reveals how polycrystalline, ill-defined structures heal into shape-selected islands of a single predominant stacking. The high crystallinity and the control on morphology and edge structure makes these graphene nanoislands ideal for their application in optoelectronics and spintronics.